If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -23 = -123 Reorder the terms: -23 + 10x = -123 Solving -23 + 10x = -123 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '23' to each side of the equation. -23 + 23 + 10x = -123 + 23 Combine like terms: -23 + 23 = 0 0 + 10x = -123 + 23 10x = -123 + 23 Combine like terms: -123 + 23 = -100 10x = -100 Divide each side by '10'. x = -10 Simplifying x = -10
| (v^2-13v-36)=0 | | -29+s=-58 | | v^2(v^2-13v-36)=0 | | 4-6p+5p= | | ax-b=cb | | 36=24N-3N^2 | | y=-30+5 | | 24N-3N^2=48N-9N^2 | | 22x^2+33x=0 | | 5(x-20)=5(x-4) | | 16+5p=51 | | -400x+4000=2000 | | -(2p-8)-6p=20+4(p+6) | | 3(h-6)=3(h+4) | | w(n)=4n+4 | | 6(2n+5)=54 | | y=12x+480 | | 5x+13=-9x | | (3x+27)(x+25)= | | n^3-5n^2-6n=0 | | 24N-3N^2-36=0 | | T-2z=2m | | 5x+19=-9x | | -4x^2+22x-30=0 | | 0.075-0.5x=x | | 96=12k | | 110+65+x=360 | | -3(q-4)+15=-5 | | -12x-2y=-28 | | -0.25a-4=1.75a-3 | | 2x+6+5x+14=180 | | 8(y+6)-3y-1= |